Hubungan Kontrol Diri dengan Motivasi Belajar Siswa Kelas XI IPA SMA Negeri 01 Tayu - Astaurina, Immelda Devi (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2023)
The research on the relationship between self-control and learning motivation of Class XI IPA students at SMA Negeri 01 Tayu is motivated by low student learning motivation, this is indicated by the results of observations and interviews of several students and counseling teachers. The formulation of the problem in this study is whether there is a significant relationship between self-control and the learning motivation of class XI IPA students at SMA Negeri 01 Tayu. The purpose of this study is to determine the relationship between self-control and learning motivation of class XI IPA students at SMA Negeri 01 Tayu. This type of research is a quantitative research with a correlational research design. The population in this study were students of class XI IPA SMA Negeri 01 Tayu with a total of 255 students. The class that became the test instrument was class XI IPS 2, and all classes XI IPA became the research sample. The sampling technique in this study was proportional random sampling. The research data were obtained from the self-control scale and learning motivation scale. Pearson product moment correlation test, it can be obtained a value of r count of 0.202. While the r table value for the number of samples is 155 with a significance level of 5% of 0.159. Therefore, the value of r count is 0.202 > r table is 0.159, it can be concluded that there is a significant relationship. Key Words: Self Control, Learning Motivation